Indonesian Ulama’s Peace Advocacy in the Palestine-Israel Conflict Following the October 7, 2023 Attack - Mudore, Syarif Bahaudin; Romadhon, Ridho (Middle Eastern Studies Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
This article examines the role of Indonesian ulama in advocating peace in the aftermath of the 7 October 2023 escalation of the Palestine-Israel conflict. Employing a qualitative approach with a library research design, the study analyzes academic literature, official statements of Islamic organizations, and public communications of ulama related to the conflict. Data analysis was conducted through initial coding, thematic analysis, and theory-driven interpretation guided by Johan Galtung’s peace-violence triangle, John Paul Lederach’s peacebuilding pyramid, and Brewer et al.’s concept of bridging social capital. The findings reveal that Indonesian ulama function as multi-level peace actors intervening in the dimensions of direct, structural, and cultural violence. Their roles are structured across leadership levels: top leadership through MUI’s political diplomacy; middle-range leadership through NU’s transnational engagement and Muhammadiyah’s humanitarian diplomacy; and grassroots leadership through solidarity mobilization by religious communities. Furthermore, ulama effectively mobilize bridging social capital within institutional, political, public, and intellectual spheres to enhance humanitarian advocacy and global peace diplomacy. Conceptually, this study contributes an integrated model of ulama engagement in networked peacebuilding across local-global scales. Practically, it recommends strengthening government and Islamic organization collaboration in religious diplomacy and peace literacy to foster a more just and humane international order.